Improving Human Resource Capacity at the Cooperatives and Micro Enterprises Service of Nganjuk Regency through Training and Development of MSME Competencies - Amelia, Frinta Indah; Hadi, Dodi Kusuma (Universitas Nusantara PGRI Kediri, 2025)
Research purposes :This study evaluates the effectiveness of training programs in improving the capacity and skills of Micro, Small, and Medium Enterprises (MSMEs). Qualitative data in the form of business income before and after training will be collected from participants from various institutions (government and non-profit) to identify the impact of training on the knowledge and skills of MSME actors. Design/Method/Approach :This study uses a qualitative approach to investigate in depth how training programs improve human resource capacity in MSMEs. Research Findings:The training program has significantly increased participants’ insight and motivation. Partnerships with the Ministry of Communication and local banks have increased the effectiveness of the training by providing better access to resources and information. Theoretical contribution/Originality:The uniqueness of this research lies in its qualitative approach, which explores participants' experiences and the effectiveness of the program in improving skills and competitiveness among MSMEs. Practical/Policy Implications:Training programs for Micro, Small, and Medium Enterprises (MSMEs) have broad and significant implications for regional and national economic development. This training can increase the capacity and competitiveness of MSMEs, thereby contributing to regional economic growth and national economic stability. In addition, this program supports financial inclusion and market access for MSMEs, which are critical to the sustainability of their businesses. Research Limitations:This study is limited to qualitative data, which may not cover all relevant aspects in the analysis of MSMEs. In addition, a long-term analysis has not been conducted, so the impact of the training program on MSMEs may not be fully visible.